A Temporal Millimeter Wave Propagation Model for Tunnels Using Ray Frustum Techniques and FFT - Choonghyen Kwon; Hayeon Kim; Haengseon Lee; Hyo Hyun Choi; Woo-jin Byun; Kwangseon Kim (International Journal of Antennas and Propagation)
A temporal millimeter wave propagation model for tunnels is presented using ray frustum techniques and fast Fourier transform (FFT). To directly estimate or simulate effects of millimeter wave channel properties on the performance of communication services, time domain impulse responses of demodulated signals should be obtained, which needs rather large computation time. To mitigate the computational burden, ray frustum techniques are used to obtain frequency domain transfer function of millimeter wave propagation environment and FFT of equivalent low pass signals are used to retrieve demodulated waveforms. This approach is numerically efficient and helps to directly estimate impact of tunnel structures and surfaces roughness on the performance of millimeter wave communication services.